Two new species of the spider genus Belisana Thorell (Araneae: Pholcidae) from Xishuangbanna, Yunnan, China - Zhao, Xiaochu; Yao, Zhiyuan; Song, Yang; Li, Shuqiang (Zootaxa, 2019)
Two new species of the spider genus Belisana Thorell, 1898 are described based on material collected in Xishuangbanna, Yunnan, China: Belisana menghai Yao & Li sp. nov. (male, female) and Belisana xishuangbanna Yao & Li sp. nov. (male), bringing the total Chinese Belisana fauna to 41 species. The DNA barcode COI of B. menghai Yao & Li sp. nov. is documented. All material studied is deposited in the Institute of Zoology, Chinese Academy of Sciences (IZCAS) in Beijing, China.